Dominating Set of Operation of Special Graphs - Hendry Dwi Saputro; Ika Hesti A.; Dafik Dafik (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2020)
A set D of vertices of a simple graph G, that is a graph without loops and multiple edges, is called a dominating set if every vertex u 2 V (G) D is adja-cent to some vertex v 2 D. The domination number of a graph G, denoted by (G), is the order of a smallest dominating set of G. A dominating set D with jDj = (G) is called a minimum dominating set. We will show dominating set of graph operation of special graph (Pn, Km, cycle Cn, Wm, ladder Ln, Btm, and special graph G1, G2.